Wireless Power Transfer System for Autonomous Driving Robot Battery Charging - Pairindra, Worapong; Khomfoi, Surin; Takorabet, Noureddine; Thounthong, Phatiphat (My University, 2023)
This paper presents a prototype of a 48V, 200W with 85 kHz wireless power transfer. The load-independent charging topology consists of an LCC/C resonant tank that provides an autonomous driving robot that is used in many industrial applications. The validation is carried out using MATLAB/Simulink and hardware implementation. The rear side battery can apparently be charged with a 15cm distance between two coils and the output voltage can be controlled at a specific level with approximately 70% efficiency.
Keywords: High Frequency Converter; LCC/C Resonant Circuit; Wireless Power Transfer